2020
DOI: 10.1111/ajt.15995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preservation solutions for static cold storage on kidney transplantation outcomes: A National Registry Study

Abstract: This study aimed to evaluate how 5 preservation solutions for static cold storage affected kidney transplant outcomes. It included all first single kidney transplants during 2010-2014 from donations after brain death in the French national transplant registry, excluding preemptive transplants and transplants of kidneys preserved with a hypothermic perfusion machine. The effects of each preservation solution on delayed graft function (DGF) and 1-year transplant failure were evaluated with hierarchical multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
0
16
1
Order By: Relevance
“…Unweighted incidences of DGF remained below 25% in all groups, with incidences <20% in IGL‐1 and UW. This is considerably lower compared to the DGF rates reported by Legeai et al (23.0% with IGL‐1, 28.9% with UW, and 35.5% with HTK) 21 . Although we do not have a clear explanation for these comparatively low DGF rates, it could be that the relatively low median cold ischemia times in our cohort compared to the cohort reported by Legeai et al contributed.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Unweighted incidences of DGF remained below 25% in all groups, with incidences <20% in IGL‐1 and UW. This is considerably lower compared to the DGF rates reported by Legeai et al (23.0% with IGL‐1, 28.9% with UW, and 35.5% with HTK) 21 . Although we do not have a clear explanation for these comparatively low DGF rates, it could be that the relatively low median cold ischemia times in our cohort compared to the cohort reported by Legeai et al contributed.…”
Section: Discussioncontrasting
confidence: 89%
“…It contradicts the main finding of a very recently published French registry study. Legeai et al report that IGL‐1 was associated with the lowest risk of DGF compared to other preservation solutions, with no differences in 1‐year eGFR and 1‐year overall graft survival; functional DGF, acute rejection, and proteinuria were not investigated 21 . As our study included outcomes of 234 IGL‐1 kidneys, it might be that any effect of IGL‐1 remained hidden as DGF rates were relatively low.…”
Section: Discussionmentioning
confidence: 84%
“…It has been previously reported that IGL-1 was not inferior to UW when evaluating islet isolation from DBD organs with short CIT [38]. Several studies demonstrated benefits of IGL-1 in preserving abdominal organs including those with long preservation time or ischemic injury [39][40][41]. When compared to UW, the protective effect of IGL-1 has been attributed to its low potassium-sodium ratio and its markedly lower viscosity, due to the use of polyethylene glycol as a colloid instead of hydroxyethyl starch, which is expected to enable higher flow rates and thus a better microcirculation [42].…”
Section: Discussionmentioning
confidence: 99%
“…Several countries have their own particular preference of solution, for example, IGL-1 is used widely in France but not in other countries. 57 …”
Section: Kidney Preservation Techniquesmentioning
confidence: 99%
“…Most recently, Legeai et al 57 reviewed the outcome of 5 different SCS solutions used for DBD kidneys in France between 2010 and 2014 (n = 7649). The majority (45.5%) were preserved using IGL-1 solution, 9.6% SCOT solution, 29% Celsior solution, 9.6% UW solution, and 5.9% HTK solution.…”
Section: Kidney Preservation Techniquesmentioning
confidence: 99%